1999
DOI: 10.1111/j.1532-5415.1999.tb01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL‐6 Level and the Development of Disability in Older Persons

Abstract: Higher circulating levels of IL-6 predict disability onset in older persons. This may be attributable to a direct effect of IL-6 on muscle atrophy and/or to the pathophysiologic role played by IL-6 in specific diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
525
3
11

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 746 publications
(563 citation statements)
references
References 48 publications
24
525
3
11
Order By: Relevance
“…Until today, only a limited number of prospective population studies further reported on the positive association between IL-6 and physical decline in older individuals. However, these previous studies were all restricted to lower age categories (Ferrucci et al 2002;Schaap et al 2009;Penninx et al 2004;Stenholm et al 2010;Taaffe et al 2000), highfunctioning persons (Schaap et al 2009;Penninx et al 2004;Taaffe et al 2000;Ferrucci et al 1999), or longer follow-up periods (Schaap et al 2009;Stenholm et al 2010;Taaffe et al 2000;Ferrucci et al 1999) or were gender-specific (Ferrucci et al 2002). Therefore, the generalizability of these findings in the oldest old might be limited.…”
Section: Discussionmentioning
confidence: 97%
“…Until today, only a limited number of prospective population studies further reported on the positive association between IL-6 and physical decline in older individuals. However, these previous studies were all restricted to lower age categories (Ferrucci et al 2002;Schaap et al 2009;Penninx et al 2004;Stenholm et al 2010;Taaffe et al 2000), highfunctioning persons (Schaap et al 2009;Penninx et al 2004;Taaffe et al 2000;Ferrucci et al 1999), or longer follow-up periods (Schaap et al 2009;Stenholm et al 2010;Taaffe et al 2000;Ferrucci et al 1999) or were gender-specific (Ferrucci et al 2002). Therefore, the generalizability of these findings in the oldest old might be limited.…”
Section: Discussionmentioning
confidence: 97%
“…Since subclinical inflammation increases the risk of cardiovascular disease, disability, neurodegenerative disorders and cancers [20][21][22][23][24], it is important to identify efficient ways to modulate low-grade immune activation. Lifestylebased interventions are one option as they have been proved to exert anti-inflammatory effects in many studies [17,32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to type 2 diabetes, subclinical inflammation is also a risk factor for cardiovascular disease, neurodegenerative disorders, depression and some cancers [20][21][22][23][24], which means that the identification of the mechanisms that modulate and attenuate systemic immune activation has widespread implications.…”
Section: Introductionmentioning
confidence: 99%
“…An evolving definition of inflammation in gerontology is low-grade activation of the innate immune system, leading to chronic production of inflammatory mediators. Inflammatory processes in general have been implicated as predictors of or contributors to chronic diseases and conditions of aging (117), such as cardiovascular disease (118), low cognitive performance (119), osteoarthritis and dementia (120), frailty (121,122), muscle wasting (123), physical performance (123,124), disability (125,126) and mortality (127)(128)(129). These associations have been…”
Section: The Biological Explanationmentioning
confidence: 99%